Globally renowned locally rooted: batik in Milan, songket in Istanbul - Abdul Rahim, Norazila; Mansor, Masaany (Faculty of Medicine, 2024)
Voice Istanbul, an international conference in all aspects of voice was held in Istanbul, Türkiye between the 25th to 28th of April 2024. It was organized by the Voice, Speech, and Swallowing Society (Türkiye) in collaboration with the Professional Voice Society, the Association of Speech and Language Therapists, and Istanbul Technical University. European Laryngological Society was also part of the invited society for Voice Istanbul 2024.